Industry's New Bottom Line on Health Care Costs: Is Less Better? - Stein, Jane (The Hastings Center report, 1985)
Corporations are developing more cost-effective payment arrangements with health care providers and are shifting costs away from expensive forms of treatment. Although employees may have fewer options as a result, quality of care need not be affected.